Modified 2016 American College of Rheumatology Fibromyalgia Criteria, the Analgesic, Anesthetic, and Addiction Clinical Trial Translations Innovations Opportunities and Networks–American Pain Society Pain Taxonomy, and the Prevalence of Fibromyalgia. Issue 5 (11th May 2021) - Häuser, Winfried; Brähler, Elmar; Ablin, Jacob; Wolfe, Frederick
Abstract : Objective: To study the prevalence of fibromyalgia (FM) in the general population according to a 2016 modification of the American College of Rheumatology criteria (FM 2016) and the Analgesic, Anesthetic, and Addiction Clinical Trial Translations Innovations Opportunities and Networks–American Pain Society pain taxonomy criteria (AAPT), and to compare diagnostic and clinical variables between the criteria sets. Methods: We studied 2, 531 randomly selected subjects from the German general population in 2019. Pain regions from the Michigan Body Map were fitted to the FM 2016 and the AAPT criteria, and criteria symptom items were derived from validated questionnaires assessing somatic and psychological symptom burden and disability. We determined FM criteria prevalence and criteria‐related scales including widespread and multisite pain (MSP) and symptom scales, and measured symptom burden and disability. Results: According to the FM 2016 criteria, the prevalence of FM was 3.4% (n = 75 subjects; 95% confidence interval [95% CI] 2.7, 4.3) compared with 5.7% (n = 130 subjects; 95% CI 4.8, 6.8) for the AAPT criteria; κ = 0.65. Compared with AAPT‐positive subjects, FM 2016–positive subjects had higher MSP, Widespread Pain Index score, Polysymptomatic Distress Scale scores, Symptom Severity Scores, and psychological symptom burden. Physician‐diagnosed FM was reported by 1.1% of the subjects. Of these, 44.0% met the FM 2016 criteria, and 47.5% met the AAPT criteria. Conclusion: The prevalence of FM in the German general population is 73% greater using the AAPT criteria than the FM 2016 criteria. The AAPT criteria select individuals with less symptom severity and fewer pain sites. The FM 2016 criteria, but not the AAPT criteria, provide a general severity measure for FM.